Výroba nosného tělesa objemovým tvářením - Dvořák, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Diplomová práce vypracovaná v rámci magisterského studia predkládá návrh výroby nosného telesa objemovým tvárením. Kování je provádeno metodou zápustkového kování na klikovém lisu LZK 1000. Ohrev je indukcní a ostrižení je provedeno na ostrihovacím lise LKOA-200. Materiál výkovku je ocel CSN 14 220. Výrobní série je 100 000 kusu. Soucástí práce jsou výpocty, návrh geometrie a ekonomické zhodnocení.

This diploma thesis has been elaborated within the Master's study that submits a production proposal of carrying body by solid forming. The forging has been performed using drop orging method at the crank forging press LZK 1000. Heating is inductive and flash trimming has been peformed in the trimming press LKOA 200. The used material of the forging is steel CSN 14 220. Production series is 100 000 pieces. A part of this thesis is calkulations, geometric design and economical evaluation.
Production of carrying body by solid forming
Keywords: Výkovek; operný držák; zápustkové kování; klikový kovací lis; zápustka.; Forging; supporting holder; drop forging; crank forging press; die.